EMOTIONAL INTELLIGENCE SKILLS AND STRESS MANAGEMENT TO ENHANCE EFFECTIVE COMMUNICATION ABILITY IN ORGANIZATIONS - Khawla Chadi; Wahiba Zellagui (International Journal of Innovative Technologies in Social Science, 2024)
The modern era is witnessing rapid transformations in the work environment, most notably the increase in professional pressures and the growing need for skills that go beyond technical expertise. This has made emotional intelligence and stress management fundamental pillars for ensuring effective and balanced workplaces. This study aims to clarify the concept of emotional intelligence and its components, analyze its relationship with stress management and effective communication, and explore its impact on improving the work environment. It also presents practical strategies to enhance emotional intelligence at both individual and institutional levels. The findings indicate that emotional intelligence directly contributes to reducing stress levels and enhancing the quality of employee interactions, which positively reflects on overall performance, job satisfaction, and the reduction of organizational conflicts. This underscores the importance of integrating these skills into professional development programs within institutions.